Utilization of Information and Communication Technology in Online Learning at School - Salim; Rahmad Prajono; Asriyani Mulia Basri; Nurhayati (FKIP Universitas Halu Oleo, 2024)
The objectives of this study are to (1) determine the portrait of the utilization of information and communication technology in online learning at SMA Negeri 1 Pasarwajo, (2) determine the response of SMA Negeri 1 Pasarwajo students to the utilization of information and communication technology in online learning, (3) analyze the implementation of online learning by utilizing information and communication technology at SMA Negeri 1 Pasarwajo. The type of research used in this study is mixed methods, namely research that combines qualitative and quantitative research. The results of this study show (1) online learning is carried out using online learning applications such as WhatsApp LMS, googgle classroom, quiper school and video conferencing with zoom and cloudX and network availability for teachers is sufficient starting from devices, data packages, and network signal connectivity; (2) students of SMA Negeri 1 Pasarwajo have a fairly good response regarding their participation in online learning by utilizing ICT; (3) the implementation of online learning shows that curriculum achievement is only 65%, teachers and students easily get learning supplements through online learning applications, teachers have difficulty in measuring attitudinal and psychomotor aspects, students have difficulty in signal accessibility and limited online learning devices.